Trouble doing two differently timed actions at once: What is the problem? - Maslovat, Dana; Klapp, Stuart T (Psychological review, 2024)
It is nearly impossible to concurrently initiate and execute two motor actions with independent timing. For example, it is difficult to tap one rhythm with the right hand while tapping a different rhythm with the left hand, even after these rhythms have been practiced individually. However, if this task is restructured so that it is represented internally as one action done by two hands rather than as two actions, one with each hand, these same rhythms can be produced easily. These findings, which indicate that motor action is limited to a single time base, are in marked contrast with the fact that it is easy to mechanically generate two independent rhythms simply by using mechanisms that are not linked to each other. After an in-depth review of the extensive research on this topic we propose a new theoretical interpretation. This attributes the difficulty to a fundamental constraint that prevents initiation of any motor action until after completion of programming the internal code that controls timing. The timing code is volatile in the sense that it must be generated immediately prior to the action to be controlled and then it must be implemented without delay. This constraint, which has been studied as it applies to single motor actions, can be extended to concurrent motor actions where it can account for the difficulty in doing two differently timed actions at once. Additional phenomena which may be attributed to this constraint are described in a concluding section. (PsycInfo Database Record (c) 2024 APA, all rights reserved).